2006
DOI: 10.1007/bf02702047
|View full text |Cite
|
Sign up to set email alerts
|

Global surface temperature in relation to northeast monsoon rainfall over Tamil Nadu

Abstract: The local and teleconnective association between Northeast Monsoon Rainfall (NEMR) over Tamil Nadu and global Surface Temperature Anomalies (STA) is examined using the monthly gridded STA data for the period 1901-2004. Various geographical regions which have significant teleconnective signals associated with NEMR are identified. During excess (deficient) NEMR years, it is observed that the meridional gradient in surface air temperature anomalies between Europe and north Africa, in the month of September is dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Studies of the NEMR variability are limited (Ramaswamy, 1972;Dhar and Rakhecha, 1983;Singh and Sontakke, 1999;Balachandran et al, 2006). Some of the previous studies related the NEMR variability with ocean-atmosphere phenomena such as El Niño/Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) (Bhanu Kripalani and Kumar, 2004;Zubair and Ropelewski, 2006;Kumar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the NEMR variability are limited (Ramaswamy, 1972;Dhar and Rakhecha, 1983;Singh and Sontakke, 1999;Balachandran et al, 2006). Some of the previous studies related the NEMR variability with ocean-atmosphere phenomena such as El Niño/Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) (Bhanu Kripalani and Kumar, 2004;Zubair and Ropelewski, 2006;Kumar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kripalani and Kumar (2004) have shown that the NEMR over the south peninsula and the IOD mode are directly related, suggesting that the positive (negative) phase of the IOD enhances (suppresses) the northeast monsoon activity. Balachandran et al (2006) have examined the local and teleconnective association between the NEMR and the global surface temperature anomalies (STAs) using the monthly gridded surface air temperature data for the period 1901-2004. They derived a zonal temperature gradient index between the eastern and western equatorial Pacific, which shows a stable significant inverse relationship with the the NEMR.…”
Section: Introductionmentioning
confidence: 99%
“…Power spectrum analysis is performed on NEM‐2015 rainfall data averaged over the box 78°–81°E, 10°–15°N, to identify the dominant periodicity (see Figure ) during the season. It is worth mentioning that the year 2015 NEM rainfall show a significant dominance of 3–6‐day periodicity which is in agreement with the EW periodicity documented in past studies (e.g., Burpee, ; ; Thorncroft and Hodges, ; Balachandran et al ., ; Geetha and Balachandran, ; Belanger et al ., ). In addition to physical and dynamical characteristics identified from Hovmöller diagram, vorticity and streamline analysis, power spectrum analysis also confirms the dominant role of EWs in occurrence of heavy rainfall events over southeast peninsular India during NEM‐2015.…”
Section: Heavy Rainfall Events Over Chennai During Nem‐2015mentioning
confidence: 99%
“…The SW and NE monsoon were studied separately by many researchers viz. Pai (2004), Rajeevan et al (2012), Balachandran et al (2006) etc. The excess or deficit SW monsoon rainfall is negatively correlated with NE monsoon rainfall (Dhar and Rakhecha, 1983;Selvaraj and Aditya, 2011).…”
Section: Introductionmentioning
confidence: 97%